Genome-wide association studies of five free amino acid levels in rice - He, Liqiang; Wang, Huixian; Sui, Yao; Miao, Yuanyuan; Jin, Cheng; Luo, Jie (Frontiers in Plant Science, 2022)
Rice (Oryza sativa L.) is one of the important staple foods for human consumption and livestock use. As a complex quality trait, free amino acid (FAA) content in rice is of nutritional importance. To dissect the genetic mechanism of FAA level, five amino acids (Val, Leu, Ile, Arg and Trp) content and 4,325,832 high quality SNPs of 448 rice accessions were used to conduct genome-wide association studies (GWAS) with nine different methods. Of these methods, one single-locus method (GEMMA), seven multi-locus methods (mrMLM, pLARmEB, FASTmrEMMA, pKWmEB, FASTmrMLM, ISIS EM-BLASSO and FarmCPU) and recent released 3VmrMLM were adopted for methodological comparison of quantitative trait nucleotide (QTN) detection and identification of stable quantitative trait nucleotide loci (QTLs). As a result, 987 QTNs were identified by eight multi-locus GWAS methods, FASTmrEMMA detected the most QTNs (245), followed by 3VmrMLM (160) and GEMMA detected the least QTNs (0). Among 88 stable QTLs identified by the above methods, 3VmrMLM have some advantages, such as the most common QTNs, the highest LOD score and the highest proportion of all detected stable QTLs. Around these stable QTLs, candidate genes were found in GO classification to be involved in primary metabolic process, biosynthetic process and catalytic activity, and showed in KEGG analysis to be participated in metabolic pathways, biosynthesis of amino acids and tryptophan metabolism. Natural variations of candidate genes resulting in the content alteration of five FAAs were identified in this association panel. In addition, 95 QTN-by-environment interactions (QEIs) of five FAA levels were detected by 3VmrMLM only. GO classification showed the candidate genes got involved in primary metabolic process, transport and catalytic activity. Candidate genes of QEIs played important roles in valine leucine and isoleucine degradation (QEI_09_03978551 and candidate gene LOC_Os09g07830 in Leu dataset), tryptophan metabolism (QEI_01_00617184 and candidate gene LOC_Os01g02020 in Trp dataset) and glutathione metabolism (QEI_12_09153839 and candidate gene LOC_Os12g16200 in Arg dataset) pathways through KEGG analysis. As an alternative of multi-locus GWAS method, these findings suggested that the application of 3VmrMLM may provide new insights into better understanding FAA accumulation and facilitate the molecular breeding of rice with high FAA level.